Analisa Efisiensi Usahatani Tumpangsari Wortel (Dacus carot L.) Dan Sawi Hijau (Bassica juncae L.) Di Kecamatan Karangpandan Kabupaten Karanganyar - Retnaningsih, Nugraheni; Dewati, Rosita; Setyarini, Agung (Universitas Veteran Bangun Nusantara, 2025)
Intercropping of carrots and green mustard greens as one type of vegetable that is suitable for cultivation in Karangpandan District, Karanganyar Regency, because of the climate, geography, and environment that are suitable, namely mountainous areas. This study aims to determine the costs, revenues, income, and efficiency of intercropping of carrots and green mustard greens per planting season in Karangpandan District, Karanganyar Regency. The method of data collection with descriptive surveys is a research method that takes samples from a population by interviewing with a questionnaire as a data collection tool. The sampling method with Quota Sampling is a sampling method based on a certain quota, which is carried out intentionally. The interview technique is also carried out with the help of filling out questionnaires by farmers. Respondents were taken from 30 intercropping farmers in Karang Village, Karangpandan District, Karanganyar Regency. The results of the study showed that the total income from intercropping of carrots and green mustard greens per planting season was Rp. 19,675,000 / Farmer. The total cost incurred by farmers per planting season was Rp. 6,651,278 /Farmer, then the average income of farmers per planting season is Rp. 13,023,722 /Farmer, R/C ratio is 2.96, while B/C ratio is 1.96. This shows that the carrot and mustard green intercropping business is efficient because > 1.